STRATEGIES TO ADDRESS EDUCATION GAPS IN REMOTE AREAS THROUGH A COMMUNITY LEARNING CENTERS APPROACH - Yeheskial A Roen; Mahrawati; Masrani Noor; Iyad Abdallah Al- Shreifeen (INJOSEDU: International Journal of Social and Education, 2025)
The use of Community Learning Centers (CLCs) as a means to address educational disparities has become an important topic in recent educational research. This study aims to analyze the effect of CLCs in improving education access and reducing education disparities in remote areas. The method used in this study involves a review of available literature from various sources, both journals and books. The results show that CLCs effectively expand access to education in remote areas and offer a valuable alternative in non-formal education. Moreover, CLCs make a significant contribution to inclusive learning and skills development, by targeting groups that are often neglected by the formal education system. These include women, ethnic minorities and adults who need new skills to adapt to changing economic conditions. However, this study also found that the sustainability of CLCs is affected by factors such as funding, staff training, and the level of local community involvement that can affect the long-term effectiveness of CLCs. The study concludes that although CLCs come with operational challenges, they remain an important tool in the global strategy to address educational disparities.